METHOD OF ESTIMATION STRESSES CONDITION IN FRONT OF THE TOE - U.G. LUDMIRSKIY; A.A. PARKHOMENKO (Advanced Engineering Research)
In article the approach to the analysis of an intense condition of a design based on division of stress on stress connected with the structural stress, a configuration of a design as a whole and with microgeometry in front of the toe, the notch stress is considered. Results of increase of fatigue durability pipe connections are submitted by change of their constructive form based on the given approach.